Pengaruh Kesempatan Kerja dan Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Kota Jambi - Lorenzo Lamas (Science of Management and Students Research Journal (SMS), 2021)
Poverty is a problem faced by all countries in the world, especially developing countries. Poverty is a complex problem that is influenced by various interrelated factors, including per capita income, unemployment, etc. Poverty is a condition which is often associated with needs, difficulties and deficiencies in various life circumstances. There are two kinds of poverty measures, namely absolute poverty and relative poverty. Absolute poverty is the inability of a person to exceed the established poverty line. Relative poverty is related to differences in the level of income of a group compared to other groups. Employment opportunities are also human capital that will increase economic growth. Employment opportunities are defined as the number of people who have occupied jobs. It is hoped that the increase in job opportunities will increase economic growth and ultimately reduce poverty levels.This study uses secondary data obtained from several agencies and services related to the title of this research. This study also uses multiple linear regression analysis tools, classical assumption test, coefficient of determination and f test and t test.The results of this study indicate that: (1) employment opportunities and economic growth have a significant simultaneous effect on the poverty level in Jambi City (2) partially employment opportunities have a positive and significant effect on the poverty level in Jambi City. (3) partial economic growth has a positive and significant effect on the level of poverty in the city of Jambi.